Inner Migrations - the private and collective in transit and relation - Westhofen, Anna (Satura, 2022)
For a long time, I imagined a place. A place in space and time that I could not map but felt strangely connected to; that called me with a far-away cry. Do you have that one place that retrieves you time and again? I do, by now. Recently, I dwelled on the likely or unlikely setting of this imagined place. A location I do not name but provide a sense of; a place to be crafted by the mind’s eye. Place-consciousness starts with the feeling we have about a place. In some places, we immediately feel at home. See, home is not necessarily a place of birth or where the family lives. The idea of home translates to the question where do we belong. Take it: the sweet coalescence of being in tune with your surroundings, others, and – most importantly – self. Now, can home equal displacement, too?